A comparative study on domestic waste disposal by landfilling and incineration in Malaysia / Rahayu Abdullah - Abdullah, Rahayu (1997)
Households, industries, institutions and commercial centres generate garbage. This solid waste is generated in large volumes in high population centres where demand for energy and resources is greatest. With increasing population, living standards, urbanization, industrialization and demand for wider varieties of consumer goods, solid waste volume is mounting. Solid waste management varies from country to country. The situation must be assessed from various angles; safety, environmental consequences, handling and economic factors must be taken into consideration. The dangers from improper site whether landfilling or incinerator which fall into the categories such as fires; gas production leadmg to possible fires, asphyxiation and explosions in buildings; leachate production leading to possible pollution of aquifers; rat and insect infestation, leading to spread of disease; and scavenging leading to a probability of injuries. So far, the focus of solid waste management programmes in Malaysia are landfilling and incineration, where between these two method, landfilling is more widely used. In order